1986
DOI: 10.1002/tox.2540010407
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological effects of creosote contamination on benthic microbial populations in an estuarine environment†

Abstract: SynopsisEcotoxicological effects of creosote contamination on benthic bacterial communities in the Elizabeth River, Virginia were investigated using both structural and functional microbial parameters. Parameters included direct counts, viable counts of heterotrophs and "cresol-utilizers", and bacterial production determined using the tritiated thymidine uptake method. Ancillary data included temperature, salinity, Eh profiles, concentrations of polycyclic aromatic hydrocarbons (PAHs), sediment granulometry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition to the evidence of toxicity, an impaired benthic community and elevated grain size‐normalized TOC were present in NBH (see “Grain size‐normalized TOC—A Tool for the Measure of Eutrophication” section and Appendix B, provided in the Supplemental Data). Both the impaired benthic community and the elevated TOC–grain size ratios are effects that may result from toxic action on organisms that either comprise a healthy community or mineralize organic C (Koepfler and Kator 1986; Zhou et al 2009). If these organisms are compromised, there will most likely be a shift in the benthic community as well as a change in the mineralization rate, and therefore a shift in the level of organic C (Zhou et al 2009) (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the evidence of toxicity, an impaired benthic community and elevated grain size‐normalized TOC were present in NBH (see “Grain size‐normalized TOC—A Tool for the Measure of Eutrophication” section and Appendix B, provided in the Supplemental Data). Both the impaired benthic community and the elevated TOC–grain size ratios are effects that may result from toxic action on organisms that either comprise a healthy community or mineralize organic C (Koepfler and Kator 1986; Zhou et al 2009). If these organisms are compromised, there will most likely be a shift in the benthic community as well as a change in the mineralization rate, and therefore a shift in the level of organic C (Zhou et al 2009) (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…A review of the current literature suggests two broad conclusions: The first, wetlands exposed to pollutants can behave in ways similar to terrestrial and aquatic systems: Species abundance and diversity can change at least temporarily; energy transmission through food networks can be altered or "shorted"; and functional parameters, resource quality, and habitat quality at the landscape level can deteriorate rapidly or subtly. Second, the lack of agreement between existing studies on specific fates and effects of pollutants on wetland processes suggests that there is little meaningful generality in wetland ecotoxicology Studies traditionally have been conducted at the population and community levels of organization, using experimental approaches and designs that resist intercomparison of results Even if these studies were in total agree ment, the relationships between many of the reported population effects to landscape functioning and the health of other ecosystems could only be suggested, and with caution Unfortunately, even with the first conclusion above, there is no reason to assume that results of ecotoxicological studies in mesocosms or other ecosystems can be generalized to predict wetland responses to pollution To a large degree, we are stuck with a lack of data explicitly dealing with toxicant effects on wetland ecology, and a major challenge for the future is to provide the needed work with a view toward understanding the functional alteration of landscapes by contaminants This challenge involves not only the development of new techniques and concepts, but also the examination of specific wetland types as organs within extended living systems, rather than as totalities studied in isolation [159,160] A further need is that relevant past and future work in this area be published in peer-reviewed journals and books It seems clear from the literature on wetland processes and functions that landscape-level manage ment approaches and quantitative cumulative-impact techniques need to be developed for specific kinds of human-wetland interactions The enormous amount of data and mapping needed to understand the ecology and toxicology of wetland complexes cannot be accommodated in traditional ways A productive approach is to organize data in a format that is accessible and understandable to a wide range of scientists, legislators, and resource managers Ths format is exemplified by the geographical information system (CIS) A CIS is a computer data structuring/presentation enwronment that allows for the geographic distribution of virtually any natural or human property to be mapped along with associated data bases With respect to studying the ecotoxicology of landscapes, an immediate need is to determine the total amounts of chemicals and other pollutants processed by the landscape on an annual basis and to what extent these quantities vary in time This approach includes (a) quantifying and tracing the sources and entry routes of agricultural contaminants (pesticides, herbicides, fertilizers), industrial chemicals (waterborne and airborne toxicants deposited in wetlands), domestic wastes (pathogens, nutrients, hazardous chemicals), and solid wastes (plastics, etc ) and (b) determining ultimate fates and effects of chemicals in each ecosystem, with mass balance Related needs include un-derstanding the significance of annual chemical loadings to the health and functioning of the various wetland types that make up the landscape over the short and long terms, and to the status of fish, wildlife, and human communities that depend on them With these data in hand, it is feasible that a CIS of a complex landscape could operate analogously to the U S Army Corps of Engineers' monitoring and control system on the Mississippi River After the initial chemical audits and environmental assessments were completed for the landscape under study, a series of monitors and experimental statio...…”
Section: General Summary and Concluding Remarksmentioning
confidence: 99%
“…In general, these communities are protected against surface-deposited hydrophobic pollutants, and studies showing changes in community activity or structure have used very high levels of toxicants (parts per thousand), sometimes in conjunction with homogenization of the sediment-pollutant mixture [ 156,1581. It has been reported that even though the activity of nitrifying bacteria is decreased by contaminants, the total numbers of specific microbial types change very little. Other studies have shown that variables such as Eh and microbial abundance, diversity, and activity are affected by high levels of toxic hydrocarbons, including PAHs, but they are not consistent between different types of ecosystems [119,159].…”
mentioning
confidence: 99%